The curse of camp cold lake - Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1997)
Sarah hates Camp Cold Lake; the lake is gross and slimy. Down by the lake someone with a see-through body is watching her.
"An Apple paperback."
"A Parachute Press book."
G2
Keywords: Horror tales; Fantasy fiction; Horror fiction